THE EFFECT OF BRAND PROMINENCE AND MUSIC INVOLVEMENT ON BRAND RECALL IN MUSIC VIDEO - Wijaya, Irenia Binardi; Cokki, Cokki (Graduate Program of Universitas Tarumanagara, 2023)
Research in developing countries is still limited, especially regarding product placement in Korean music. This study aims to determine the effect of brand prominence and music involvement on brand recall. This study used the pre-test and post-test experimental method. The Korean music video, namely